More than Telling a Story: A Closer Look at the Process of Transforming Data into Visually Shared Stories - Lee, Bongshin; Henry Riche, Nathalie; Isenberg, Petra; Carpendale, Sheelagh (In IEEE CG&A journal (Visualization Viewpoints), 2015)
Visualizations are increasingly used “in the wild” to tell compelling stories supported by data. Examples include Hans Rosling’s talks on human development trends using Gapminder (gapminder.org) and the use of visualizations on the web (e.g., Figure 1) including news media such as the New York Times 1 and the Guardian 2 . Given the practical power visualizations can have in communicating facts and opinions, the visualization research community has begun to pay more attention to the need and use of visualization as a storytelling medium to tell compelling data stories.